A Question of Strategic Legislation: Can the EU deal with cybersecurity issues in space? - Francesco Cappelletti; Vangelis Papakonstantinou (International Telecommunications Society (ITS), 2023)
This paper explores the impact of novel and forthcoming regulations on the European Union's (EU) strategic projection, focusing on space systems and their wide-ranging effects on services for European citizens and related industries. By examining space legislation and cybersecurity, this research provides an analytical perspective on whether the EU has strategically implemented regulations in shared competency fields like space and international security. While European Member States face challenges in implementing national space strategies, the EU's relevance extends beyond internal market and industry considerations, showcasing the Union's capabilities in implementing what this study defines as 'strategic regulations' in shared competencies, including international security.
Keywords: 330